Comparative effectiveness of biliary brush cytology and intraductal biopsy for detection of malignant biliary strictures: a systematic review and meta-analysis - Navaneethan, Udayakumar (Gastrointest Endosc, 2014)
BACKGROUND: Evaluation of indeterminate biliary strictures typically involves collection and analysis of tissue or cells. Brush cytology and intraductal biopsies that are routinely performed during ERCP to assess malignant-appearing biliary strictures are limited by relatively low sensitivity. OBJECTIVE: To study the comparative effectiveness of brushings for cytology and intraductal biopsies in the etiology of biliary strictures. DESIGN: Meta-analysis. SETTING: Referral center. PATIENTS: PUBMED and Embase databases were reviewed for studies published to April 2014 where diagnostic correlation of histology was available. INTERVENTION: Database and review of study findings. MAIN OUTCOME MEASUREMENTS: Sensitivity and specificity. RESULTS: The pooled sensitivity and specificity of brushings for the diagnosis of malignant biliary strictures was 45% (95% confidence interval [CI], 40%–50%) and 99% (95% CI, 98%–100%), respectively. The pooled diagnostic odds ratio to detect malignant biliary strictures was 33.43 (95% CI, 14.29–78.24). For intraductal biopsies, the pooled sensitivity and specificity were 48.1% (95% CI, 42.8%–53.4%) and 99.2% (95% CI, 97.6%–99.8%), respectively. The pooled diagnostic odds ratio to detect malignant biliary strictures was 43.18 (95% CI, 19.39–95.83). A combination of both modalities only modestly increased the sensitivity (59.4%; 95% CI, 53.7%–64.8%) with a specificity of 100% (95% CI, 98.8%–100.0%). The Begg-Mazumdar and Egger tests indicated a low potential for publication bias. LIMITATIONS: Inclusion of low-quality studies. CONCLUSION: Our study suggests that both brushings and biopsy are comparable and have limited sensitivity for the diagnosis of malignant biliary strictures. A combination of both only modestly increases the sensitivity.